2018
DOI: 10.4066/biomedicalresearch.54-18-598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starvation on expression of troponin complex genes and ER stress associated genes in skeletal muscles

Abstract: Little is known about the mechanism of gene expression changes in skeletal muscle during starvation. This study investigated the influence of starvation on gene expression of troponin complex (TnC, TnI and TnT), tropomyosin (Tpm), and endoplasmic reticulum (ER) stress associated proteins (BiP, calreticulin, PDI, and ATF6) in three kinds of skeletal muscles of Gryllus bimaculatus. Dorsal ventral flight muscle (DVM), dorsal longitudinal, and dorsal wing flight muscles (DWM) were identified as typical skeletal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…The present study found upregulated expression of Hdh-TPM during the first week of starvation in the mantle and muscle tissues. In crickets, upregulated expression of TPM was also previously reported during short-term starvation [52]. However, after the first week, the expression of Hdh-TPM significantly increased in the mantle and decreased in the muscle (not significant) until refeeding.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The present study found upregulated expression of Hdh-TPM during the first week of starvation in the mantle and muscle tissues. In crickets, upregulated expression of TPM was also previously reported during short-term starvation [52]. However, after the first week, the expression of Hdh-TPM significantly increased in the mantle and decreased in the muscle (not significant) until refeeding.…”
Section: Discussionsupporting
confidence: 70%
“…Starvation is one of the common nutritional stresses that can affect abalone body physiology, by influencing the expression of several genes [52]. The present study found upregulated expression of Hdh-TPM during the first week of starvation in the mantle and muscle tissues.…”
Section: Discussionsupporting
confidence: 58%